2019
DOI: 10.1177/2049463719886890
|View full text |Cite
|
Sign up to set email alerts
|

Sensory mapping of lumbar facet joint pain: a feasibility study

Abstract: Objective: To evaluate the feasibility of sensory mapping of lumbar facet joint pain in patients scheduled to undergo radiofrequency (RF) denervation. Design: Prospective cohort study. Setting: University teaching hospital. Subjects: A total of 15 participants listed for RF denervation of lumbar facet joint. Method: After written informed consent, participants were recruited to the study. Participants completed a pain diagram prior to their procedure. After successful image-guided placement of RF cannulas, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Takahashi et al 13 found that the nerve fibers of L1-L5 dorsal root ganglia joins nerve, suppling the rat’s L5-S1 LFJ, by retrograde nerve tracing method. Kanakarajan et al 14 used suprathreshold sensory stimulation to map facetogenic LBP, and they found suprathreshold stimulation of target nerves completely covered the usually painful area in 14 of 15 participants. Among them, 9 patients felt pain or paresthesia during suprathreshold stimulation, exceeding the normally painful area.…”
Section: Anatomy Of Lfjmentioning
confidence: 99%
“…Takahashi et al 13 found that the nerve fibers of L1-L5 dorsal root ganglia joins nerve, suppling the rat’s L5-S1 LFJ, by retrograde nerve tracing method. Kanakarajan et al 14 used suprathreshold sensory stimulation to map facetogenic LBP, and they found suprathreshold stimulation of target nerves completely covered the usually painful area in 14 of 15 participants. Among them, 9 patients felt pain or paresthesia during suprathreshold stimulation, exceeding the normally painful area.…”
Section: Anatomy Of Lfjmentioning
confidence: 99%